HACKING THE SALAFI-WAHABI MOVEMENT IN MANADO – INDONESIA - Rajafi, Ahmad; Ladiqi, Suyatno; Hamhij , Naili Adilah (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to examine the reasoning process associated with transforming fiqhiyyah into i'tiqadiyyah by the salafi-wahabi groups in Manado, Indonesia. Fiqh (jurisprudence) and aqidah (faith) are different entities with both measured based on the science of ushul fiqh, and usul al-din, respectively. However, under the Salafi-Wahabi group, reasoning fiqhiyyah was transformed into i'tiqadiyyah through a generalistic paradigm, using an exclusive movement. The three major groups of salafi-wahabi are Wahdah Islamiyah, the Komok Luar As-Sunnah Mosque community, and several personnel from Hidayatullah. The recitation theme which is based on purification was obtained from Quran and al-Hadith consisting of shahih. Therefore, from these reasoning, the rites derived from ijtihad are doubted for validity in the authentic hadith and classified as a heresy with pervert implications. This led to a social conflict without physical contact with Muslims finding it difficult to unite with the Christian community as the majority group.